Factors driving changes in freshwater mussel (Bivalvia, Unionida) diversity and distribution in Peninsular Malaysia - Zieritz, Alexandra; Lopes-Lima, Manuel; Bogan, Arthur E.; Sousa, Ronaldo; Walton, Samuel; Khairul Adha, A. Rahim; Wilson, John James; Ng, Peiyin; Froufe, Elsa; McGowan, Suzanne (Elsevier, 2016)
Freshwater mussels (Bivalvia, Unionida) fulfil important ecosystem functions and are one of the most threatened freshwater taxa globally. Knowledge of freshwater mussel diversity, distribution and ecology in Peninsular Malaysia is extremely poor, and the conservation status of half of the species presumed to occur in the region has yet to be assessed. We conducted the first comprehensive assessment of Peninsular Malaysia's freshwater mussels based on species presence/absence and environmental data collected from 155 sites spanning all major river catchments and diverse habitat types. Through an integrative morphological-molecular approach we recognised nine native and one widespread non-native species, i.e. Sinanodonta woodiana. Two species, i.e. Pilsbryoconcha compressa and Pseudodon cambodjensis, had not been previously recorded from Malaysia, which is likely a result of morphological misidentifications of historical records. Due to their restriction to single river catchments and declining distributions, Hyriopsis bialata, possibly endemic to Peninsular Malaysia, Ensidens ingallsianus, possibly already extinct in the peninsula, and Rectidens sumatrensis, particularly require conservation attention. Equally, the Pahang, the Perak and the north-western river catchments are of particular conservation value due to the presence of a globally unique freshwater mussel fauna. Statistical relationships of 15 water quality parameters and mussel presence/absence identified acidification and nutrient pollution (eutrophication) as the most important anthropogenic factors threatening freshwater mussel diversity in Peninsular Malaysia. These factors can be linked to atmospheric pollution, deforestation, oil-palm plantations and a lack of functioning waste water treatment, and could be mitigated by establishing riparian buffers and improving waste water treatment for rivers running through agricultural and residential land.